Efficacy and toxicity of linear polyamidoamine polymers used in gene delivery - Almulathanon, Ammar (2018)
Introduction: Interestingly, polyamidoamines (PAAs) are a group of biodegradable cationic polymers that exhibit a transfection efficiency comparable to that obtained with PEI but with a low cytotoxicity compared to other polycationic vectors. However, their cellular adverse effects have only been probed in assays indirectly measuring the cell metabolic activity based on the reduction of tetrazolium salts into coloured formazan derivatives by mitochondrial enzymes such as the MTT, MTS or XTT assays. There is therefore a need for a deeper insight into their cytotoxic profile before their potential as delivery agents in gene therapy can be fully appreciated. Furthermore, the intracellular fate of PAA polyplexes remains unclear to date, prompting questions around the mechanisms underlying their ability to mediate gene transfer. The present work explored cellular events induced by DNA polyplexes prepared using a linear PAA with a methylenebisacrylamide/dimethylethylenediamine (MBA-DMEDA) backbone of a molecular weight over 10kDa with the aim to confirm and better understand the absence of relationship between cytotoxicity and transfection efficiency reported with those vectors. Methods: Complexes were formed between pDNA and branched polyethyleneimine (BPEI, 25 kDa) or various PAAs including a homopolymer of a molecular weight >10 kDa (HP->10), a PEGylated Triblock Copolymer (CP) and a blend of CP and HP->10 to form a bioreducible cross-linked delivery system. Physicochemical properties of pDNA polyplexes were analysed by using simple techniques including gel electrophoresis, dynamic light scattering (DLS) and zeta potential measurement. The transfection efficiency of pDNA complexes was compared in A549 cells using a luciferase reporter gene assay. The impact of endo/lysosomal escape on transfectionefficiency of pDNA polyplexes was investigated by transfecting cells in presence of bafilomycin A1 or chloroquine, whereas the role of reactive oxygen species in transgene expression was evaluated by using hydroquinone as antioxidant. Cytotoxicity caused by the vectors was evaluated by measuring cell metabolic activity, lactate dehydrogenase release, formation of reactive oxygen species and changes in mitochondrial membrane potential. Results: Gel electrophoresis showed complete incorporation of pDNA by individual and cross linked PAA polyplexes at a similar polymer to DNA (RU:Nt) ratio of (2:1). In comparison, pDNA incorporation was achieved by BPEI at a 3:1 RU:Nt ratio. All polymers were able to condense pDNA into nanoparticles of ≤200 nm in diameter with a positive surface charge. Non-PEGylated PAA polyplexes showed higher luciferase activity than the PEGylated counterparts, but lower than that of BPEI. However, in contrast to BPEI vectors, PAA polyplexes caused negligible cytotoxic effects. The transfection efficiency of PAA polyplexes was significantly reduced in presence of bafilomycin A1 while chloroquine either enhanced or decreased transgene expression depending on the RU:Nt. No changes were found in the transfection of PAA polyplexes in the presence of hydroquinone compared to BPEI. Conclusions: PAA polyplexes displayed a pH-dependent endo/lysosomal escape which was not associated with cytotoxic events, unlike observed with BPEI polyplexes. This is likely due to their greater interactions with biological membranes at acidic than neutral pH. The presence of excess polymer is considered necessary for improving transfection efficiency of PAA polyplexes. PAA was identified as promising and safe candidate for in vitro gene delivery and has potential for future in vivo gene therapy.